대학교 교양 교과에서 외국인 유학생을 위한 블렌디드 러닝 수업 운영의 효과 및 한계 연구 －온라인과 오프라인 강의의 비교를 중심으로 - 김강희 (교양교육연구, 14(5), 2020)
본 연구는 대학 수업에서 온라인과 오프라인 환경을 병행하는 블렌디드 러닝 수업의 효과와 한계를고찰하는 데에 목적이 있다. 이를 위하여 본 연구에서는 동일한 교과목을 (가) 전체 오프라인, (나) 온라인과 오프라인의 혼합, (다) 전체 온라인으로 3학기에 걸쳐 운영하였으며, 이의 비교를 통해 블렌디드 러닝 수업의 효과 및 한계를 분석하고자 하였다. 그 결과는 다음과 같다. 첫째, 시험 성적에 있어 온라인과 오프라인을 혼합한 블렌디드 러닝 수업이 전체 온라인 수업보다통계적으로 높은 성취를 보이는 것으로 조사되었다. 둘째, 전체 온라인으로 진행한 수업에서 학습자간의 성적 편차가 가장 크게 발생한 것으로 조사되었다. 셋째, 전체 오프라인으로 진행한 수업이 중간고사에 비해 기말고사에서 학습자들의 성적 향상도가 가장 높은 것으로 나타났다. 이러한 조사 결과는 온라인 강의의 효율성에도 불구하고 학습자 간 편차에는 교사와의 상호작용이이루어지는 오프라인 강의가 효과적이라는 점을 보여주고 있다. 따라서 온라인 강의와 오프라인 강의를병합한 블렌디드 러닝 수업을 통해 온⋅오프라인의 한계를 보완할 필요가 있으며, 이러한 노력이 복합적으로 작용할 때에야 비로소 온라인을 통한 학습자 중심의 자기주도적 학습이 효과적으로 이루어질수 있을 것이다. The purpose of this study was to examine the effects and limitations of blended learning-based lectures in online and offline environments. In order to accomplish the purpose of this study, a lecture course was conducted using (a) an entirely offline approach (b) one combining online and offline methods, and (c) an approach taking place entirely online over three semesters. From the results of these three methods, we sought to analyze the effects and limitations of blended learning-based lectures. First, students who received lectures both online and offline performed statistically significantly better than students who only received online lectures. Second, students who only received online lectures had the greatest variation in their test scores. Third, students who only received offline lectures had the greatest improvement in test scores between their mid-term and final exams. Online lectures alone do not produce the best learning outcomes. In-person intervention and guidance from teachers offered in blended courses can improve our students’ self-directed learning. KCI Citation Count: 0